Peran Media Sosial dalam Pembentukan Persepsi Publik terhadap Kebijakan Pemerintah - Nugraha, Ahmad Fikri; Putri, Siti Rahmawati; Wibowo, Dwi Prasetyo (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Social media has emerged as a digital public sphere that significantly influences the formation of public perceptions of government policies. Advances in communication technology enable two-way interaction between governments and citizens while accelerating the dissemination of information and opinions. This article aims to comprehensively analyze the role of social media in shaping public perceptions of government policies by examining communication patterns, public sentiment, and dynamics of digital political participation. This study employs a qualitative approach through a systematic literature review of reputable international and national scholarly articles related to social media, public opinion, and public policy. The findings indicate that social media functions as a strategic instrument for policy communication, a platform for articulating public aspirations, and a real-time public opinion monitoring tool. However, social media also presents serious challenges, including disinformation, polarization, opinion manipulation, and the creation of echo chambers that may undermine democratic quality. These findings highlight the importance of digital literacy, adaptive public communication governance, and ethical use of social media analytics within the public policy cycle. This article contributes theoretically and practically to the development of public policy and government communication studies in the digital era.